2010
DOI: 10.1097/mpg.0b013e3181b18308
|View full text |Cite
|
Sign up to set email alerts
|

Fat Malabsorption in Cystic Fibrosis: Comparison of Quantitative Fat Assay and a Novel Assay Using Fecal Lauric/Behenic Acid

Abstract: Objectives-The "gold standard" for the diagnosis of fat malabsorption, the 72 hour fat balance study, requires a three day collection to generate a coefficient of fat absorption (CFA). We hypothesized that, a new test using behenic acid (behenate test) as a nonabsorbable lipid marker may provide a facile means to assess fat absorption. The study proposed to answer two questions: 1) whether the "behenate test" correlated with the "gold standard" and 2) whether the CFA improved when taking pancreatic enzymes dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 27 publications
0
21
0
1
Order By: Relevance
“…In adult patients with chronic pancreatitis, Dominguez‐Munoz et al in 2005 showed, using the C mixed triglyceride breath test, that enzymes taken with meals or at the end of the meal improved fat absorption compared with when taken before meals. In contrast, Dorsey et al in 2010, showed in CF and PI that there was no difference in the CFA when enzymes were taken during meals or before meals . The difference in these results may be related to the various methodologies used, diagnosis, disease severity, and that the CFA is not a highly reliable test.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In adult patients with chronic pancreatitis, Dominguez‐Munoz et al in 2005 showed, using the C mixed triglyceride breath test, that enzymes taken with meals or at the end of the meal improved fat absorption compared with when taken before meals. In contrast, Dorsey et al in 2010, showed in CF and PI that there was no difference in the CFA when enzymes were taken during meals or before meals . The difference in these results may be related to the various methodologies used, diagnosis, disease severity, and that the CFA is not a highly reliable test.…”
Section: Discussionmentioning
confidence: 96%
“…With these limitations, CFA is underutilized or avoided in most clinical care and research settings. Several alternative tests for assessment of fat malabsorption have been explored including mixed triglyceride, dipeptide breath tests, stable and radioactive isotope tests, spot stool fat level, stool behenate levels, secretin‐cholecystokinin–stimulated pancreatic challenge test, and secretin‐stimulated magnetic resonance cholangiopancreatography . All have limitations and have failed to gain wide acceptance as accurate or practical alternatives to the 72‐hour stool and diet collection.…”
mentioning
confidence: 99%
“…SPB is a component of fat used in commercial production of fried snack foods and serves as a nonabsorbable lipid marker. The stool lauric acid: behenic acid ratio provides an assessment of fat absorption which correlates with CFA, but it is not sufficiently robust to replace CFA …”
Section: Exocrine Pancreatic Insufficiencymentioning
confidence: 99%
“…The stool lauric acid: behenic acid ratio provides an assessment of fat absorption which correlates with CFA, but it is not sufficiently robust to replace CFA. 75 Treatment of PI. The objectives of pancreatic enzyme replacement therapy (PERT) are to correct macro-and micronutrient maldigestion, alleviate abdominal symptoms attributable to maldigestion, help establish normal stools and bowel habits, and sustain normal growth and nutritional status.…”
Section: Diagnosis Of Pimentioning
confidence: 99%
“…Without treatment, fat malabsorption leads to malnutrition, failure to thrive, fat-soluble vitamin (A, D, E, and K) inadequacy, and essential fatty acid deficiency (EFAD) (40,96).…”
Section: Introductionmentioning
confidence: 99%